Impact of COVID-19 pandemic on urology practice: A single-center experience - Caner Baran (Ukrainian Journal of Nephrology and Dialysis, 2021)
The present study aimed to evaluate the impact of the Coronavirus disease (COVID-19) pandemic on the urology outpatient clinic and provide objective data for the allocation of the resources during the pandemic. Materials and methods. The patient records who were admitted to our Hospital Urology outpatient clinic during March 20th - May 29th, 2019, and March 20th - May 29th, 2020 has been evaluated and constituted two groups as Non-Pandemic Group and Pandemic Group according to application date. Groups have been compared according to demographic and cohort-specific variables.Results. There has been a statistically significant difference between groups according to age, gender, admission, prescription, and hospitalization rates. During the pandemic period, we found that the rates of patient admission, frequency and the number of hospitalizations decreased, and the rate of prescribing increased. Also, we found that male patients aged 18-65 years were admitted more frequently during the pandemic period.The analysis of the subgroups constituted according to diagnostic segmentation revealed that the patients with lower urinary tract symptoms and pediatric urology patients decreased while infertility and infection groups were increased. Conclusion. The urology outpatient clinic has been affected by the COVID-19 pandemic from various perspectives. This alteration should take into consideration for the planning of the services during a pandemic.